Ending hunger in our lifetime: food security and globalization - Runge, C. Ford; Senauer, Benjamin; Pardey, Philip G.; Rosegrant, Mark W. (International Food Policy Research Institute, 2003)
This book was written at a hinge in history. It began with generous support from the Ford Foundation in the late 1990s, during a period of unparalleled prosperity in the rich countries but persistent poverty and hunger in many poor ones. It was completed in the wake of growing economic and political instability, civil society discontent, and the terrorist attacks in New York and Washington, all of which contributed to the growing unease over the relationship between the world's rich and poor. This book provides a vision for a multilateral approach to addressing global hunger problems.